Hormonal correlates of the annual cycle of activity and body temperature in the South-American tegu lizard (Salvator merianae) - Zena, Lucas A.; Dillon, Danielle; Hunt, Kathleen E.; Navas, Carlos A.; Buck, C. Loren; Bicego, Kenia C. [UNESP] (Elsevier B.V., 2020)
Life history transitions and hormones are known to interact and influence many aspects of animal physiology and behavior. The South-American tegu lizard (Salvator merianae) exhibits a profound seasonal shift in metabolism and body temperature, characterized by high daily activity during warmer months, including reproductive endothermy in spring, and metabolic suppression during hibernation in winter. This makes S. merianae an interesting subject for studies of interrelationships between endocrinology and seasonal changes in physiology/behavior. We investigated how plasma concentrations of hormones involved in regulation of energy metabolism (thyroid hormones T-4 and T-3; corticosterone) and reproduction (testosterone in males and estrogen/progesterone in females) correlate with activity and body temperature (Tb) across the annual cycle of captive held S. merianae in semi-natural conditions. In our initial model, thyroid hormones and corticosterone showed a positive relationship with activity and Tb with independent of sex: T-3 positively correlated with activity and Tb, while T-4 and corticosterone correlated positively with changes in Tb only. This suggests that thyroid hormones and glucocorticoids may be involved in metabolic transitions of annual cycle events. When accounting for sex-steroid hormones, our sex separated models showed a positive relationship between testosterone and Tb in males and progesterone and activity in females. Coupling seasonal endocrine measures with activity and Tb may expand our understanding of the relationship between animal's physiology and its environment. Manipulative experiments are required in order to unveil the directionality of influences existing among abiotic factors and the hormonal signaling of annual cyclicity in physiology/behavior.
Keywords: Activity; Body temperature; Corticosterone; Hibernation; Progesterone; Testosterone; Thyroid hormones